Biogas production pretreatment methods in anaerobic digestion - Mudhoo, Ackmez (Wiley ; Scrivener, 2012)
The anaerobic digestion of sewage sludge has long been used for solids reduction by wastewater treatment facilities, but has gained recognition as a form of energy production. Biogas is formed as a byproduct of anaerobic digestion and is composed mostly of methane and carbon dioxide with other trace elements. The focus of this thesis is the enhancement of biogas production through the optimization of the anaerobic digestion of sewage sludge. Batch experiments showed that digest pH is indicative of the current stage of digestion. This will provide wastewater treatment facilities with a way to monitor digester activity, as each stage of digestion was identified through constant pH monitoring. The digestion process was optimized through various parametric studies designed to determine the effect of each parameter and find an optimal range for operation. The optimum range for pH was 7.0-7.5.-Testing of temperature showed that the mesophilic range (30-40°C) provided the highest, most constant gas production. Alkalinity adjustment with magnesium hydroxide increased both pH and alkalinity. Biogas production was highest in samples with alkalinity ranging from 2,000-2,500 mg/L as CaCO_3 . Volatile fatty acid (VFA) adjustment with sodium propionate increased both alkalinity and VFA content within the digest. High levels of VFA caused digestion to struggle while small adjustments showed an increase in production. Pressure measurement showed that an increase in pressure during digestion improved both the quality and quantity of produced biogas. Semi-continuous experimentation showed consistent biogas production. However, high VFA content resulted in poor gas quality. Digester energy balances completed at the Hilliard-Fletcher Wastewater Treatment Plant showed that 1,705 m^3/day biogas are required for daily operation (basis: 60:40 ratio CH_4 :CO_2).-Parametric tests showed the ability to provide up to 1,944 m^3/day at a methane content of 80%. Increasing the methane content from 60 to 80% increases the heating value of the gas by one-third, requiring less gas for daily operation. This allows for better energy efficiency. All gas volumes are reported at atmospheric pressure and a temperature of 35°C. Future work will focus on the effect of pressure to identify the extent with which it affects digestion.
Keywords: Sewage -- Purification -- Anaerobic treatment.; elektronické knihy; electronic books